P3_1 Feeling Lucky? - Phong, Allen; Searle, Thomas; McNally, Michael; Pierce, Robert (Physics Special Topics, 2011)
When playing the popular casino game Blackjack, the odds of getting a “blackjack” are quite low. The online gambling industry is growing rapidly, so when playing Blackjack online and the computer manages to win by getting multiple blackjacks in a row, was it due to “luck” or was the computer program cheating?